2017
DOI: 10.1111/tmi.12885
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural disinhibition in the general population during the antiretroviral therapy roll‐out in Sub‐Saharan Africa: systematic review and meta‐analysis

Abstract: Abstractobjectives Improved life expectancy and reduced transmission probabilities due to ART may result in behavioural disinhibition -that is an increase in sexual risk behaviour in response to a perceived lower risk of HIV. We examined trends in sexual risk behaviour in the general population of subSaharan African countries 1999-2015.methods We systematically reviewed scientific literature of sexual behaviour and reviewed trends in Demographic and Health Surveys. A meta-analysis on four indicators of sexual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…And finally we observed a decrease over calendar time in the proportion of men reporting two or more sexual partners in the past six months and of concurrency. This time trend is however different from what was found in a recent meta-analysis, where reporting multiple partners over the past 12 months increased consistently across almost all study countries30 .…”
contrasting
confidence: 99%
“…And finally we observed a decrease over calendar time in the proportion of men reporting two or more sexual partners in the past six months and of concurrency. This time trend is however different from what was found in a recent meta-analysis, where reporting multiple partners over the past 12 months increased consistently across almost all study countries30 .…”
contrasting
confidence: 99%
“…Although our data demonstrate that condom use continues to be inconsistent among this study population, overall data from the Demographic and Health Surveys (DHS) in sub-Saharan Africa suggests increased condom use over the last one to two decades 10. Most participants recognise that condoms reduce HIV transmission risk; however, safe sexual practices seem to be influenced more by other factors, such as relationship dynamics, fertility intention and self-efficacy than perception of infection or transmission risk.…”
Section: Discussionmentioning
confidence: 57%
“…A limited number of studies in eastern and southern Africa found optimistic beliefs about HIV due to ART associated with risky sexual behaviour . A review and analysis of nationally representative data from sub‐Saharan Africa found increasing multiple and transactional sexual partnerships but also decreasing condomless sexual intercourse . It is therefore unclear whether and to what extent changes in sexual behaviour have led to increased numbers of people exposed to elevated HIV/STI risks.…”
Section: Introductionmentioning
confidence: 99%